2006
DOI: 10.1002/spe.707
|View full text |Cite
|
Sign up to set email alerts
|

Generating content and display of library catalogue cards using XML technology

Abstract: This paper presents the use of XML technology in modelling library documents, i.e. catalogue cards (and the type of reports) found in a library information system. The method of schema formation for content of various types of library catalogue cards is also described. The display of catalogue cards has been done based on described schemas. The display process has been performed in two steps. The first one extracts the content from a bibliographical record based on the schema describing catalogue card concepts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…In the work ( Jakšić, 2004), it is shown that UNIMARC format, as well as the bibliographic record within the UNIMARC format, can be described by the XMLSchema language. The generation of catalogue cards based on the XML bibliographic record is described in the paper (Vidaković and Racković, 2006). Quality control of the XML bibliographic records in the UNIMARC format is described in the paper (Budimir and Surla, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the work ( Jakšić, 2004), it is shown that UNIMARC format, as well as the bibliographic record within the UNIMARC format, can be described by the XMLSchema language. The generation of catalogue cards based on the XML bibliographic record is described in the paper (Vidaković and Racković, 2006). Quality control of the XML bibliographic records in the UNIMARC format is described in the paper (Budimir and Surla, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the paper [3], it is shown that UNIMARC format, as well as the bibliographic record within the UNIMARC format, can be described by the XMLSchema language. The generation of catalogue cards based on the XML bibliographic record is described in the paper [4]. Quality control of the XML bibliographic records in the UNIMARC format is described in the paper [5].…”
Section: Introductionmentioning
confidence: 99%
“…A master thesis [5] includes modelling and implementation of an UNIMARC format XML editor. Modelling of bibliographic cataloguing cards using XML technology, based on XML bibliographic records, is shown in [6] Concepts and contents of various cataloguing cards are described using XML schema language. A quality control system for bibliographic records based on XML schema modelling and XSLT and XPath programming languages are described in [7].…”
Section: Introductionmentioning
confidence: 99%